What is the Added Value of Preschool? Long-Term Impacts and Interactions with a Health Intervention - Maya Rossin-Slater; Miriam Wüst (Institute for the Study of Labor (IZA), 2016)
We study the impact of targeted high quality preschool over the life cycle and across generations, and examine its interaction with a health intervention during infancy. Using administrative data from Denmark together with variation in the timing of program implementation between 1933 and 1960, we find lasting benefits of access to preschool at age 3 on outcomes through age 65 – educational attainment increases, income rises (for men), and the probability of survival increases (for women). Further, the benefits persist to the next generation, who experience higher educational attainment by age 25. However, exposure to a nurse home visiting program in infancy reduces the added value of preschool. The positive effect of preschool is lowered by 85 percent for years of schooling (of the first generation) and by 86 percent for adult income among men.
Keywords: I38; I14; J13; 330; preschool; intergenerational; interactions